2022
DOI: 10.52215/rev.bgs.2022.83.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pollution with heavy metals and petroleum products in the sediments of Varna Lake

Abstract: We present the results from the first large-scale study on pollution in the Varna Lake sediments, which was implemented in two preselected zones with significant importance for developing economic activities and urban planning. Based on 140 probes, we developed a digital map of the pollution gradients in these zones. The sediment analysis shows that the pollution levels at specific locations significantly exceed the international standards for contamination with heavy metals and petroleum products. The reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…After an analysis of the average contamination of all samples from the two areas of interest, it was observed that the most significant accumulation of iron, lead and copper is in Zone 1, and the highest pollution in Zone 2 is due to arsenic, mercury and petroleum products Figure 2. The accumulation of these heavy metals and petroleum products in the sediments of Varna Lake is due to the solid industrial pressure, urbanisation and shipping [3]. After a comparison of the average values of pollution in the two zones, it was observed that the indicators -mercury, copper and petroleum products prevail over the others.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…After an analysis of the average contamination of all samples from the two areas of interest, it was observed that the most significant accumulation of iron, lead and copper is in Zone 1, and the highest pollution in Zone 2 is due to arsenic, mercury and petroleum products Figure 2. The accumulation of these heavy metals and petroleum products in the sediments of Varna Lake is due to the solid industrial pressure, urbanisation and shipping [3]. After a comparison of the average values of pollution in the two zones, it was observed that the indicators -mercury, copper and petroleum products prevail over the others.…”
Section: Resultsmentioning
confidence: 98%
“…Another reason for the difference in the contamination could be that in Channel 1, periodic dredging of the bottom is carried out to provide a navigable depth Figures 3 and 4. Given the direction of movement of the lake waters and the location of the dredged material dump, there is a possibility that fine sediments and their pollutants are transported to the Old Channel [3]. All accumulated pollutants in the sediments of Varna Lake are continuously released into the water body and contribute to maintaining its poor ecological condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations